Pengembangan Storyboard Game Sekolah - Ramadhani, Rifqi; Mukhammad, Zaki; Pratama, Tegar Aditia; Yaqin, M. Ainul (STIKOM Tunas Bangsa Pematangsiantar, 2020)
The school is a very important place of learning for every Indonesian citizen. Receiving education is the right of Indonesian citizens who have been guaranteed by the 1945 Constitution. Therefore, every Indonesian citizen has the right to get an easily accessible and quality education. To go to quality schools, each school must meet National Education Standards. Meeting the quality standards of schools needs to implement rules that are expected to increase the quality of each school. The rule then needs to be tested which sometimes the process is very long and prone to failure in the middle of the rule is applied. In this study, researchers created a school game storyboard that is expected to help the process of testing a rule so that it does not need to take a very long time. From the results of the storyboards that have been made it can be seen that building a quality school must be started and arranged from level 1.